2014
DOI: 10.1103/physrevb.89.075429
|View full text |Cite
|
Sign up to set email alerts
|

Orbital entanglement and electron localization in quantum wires

Abstract: We study the signatures of disorder in the production of orbital electron entanglement in quantum wires. Disordered entanglers suffer the effects of localization of the electron wave function and random fluctuations in entanglement production. This manifests in the statistics of the concurrence, a measure of the produced two-qubit entanglement. We calculate the concurrence distribution as a function of the disorder strength within a randommatrix approach. We also identify significant constraints on the entangl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Quantum correlations are at the very heart of quantum physics [1] and of applications like quantum computing and quantum cryptography [2]. The ability of quantum transport devices to produce and manipulate entanglement has been explored during the last years [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Several of those devices produce orbital entanglement from scattering processes taking place inside one of its parts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantum correlations are at the very heart of quantum physics [1] and of applications like quantum computing and quantum cryptography [2]. The ability of quantum transport devices to produce and manipulate entanglement has been explored during the last years [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Several of those devices produce orbital entanglement from scattering processes taking place inside one of its parts.…”
Section: Introductionmentioning
confidence: 99%
“…Constraints on entanglement production imposed by the geometry of the device were explored [10], and it was found that more entangled states are less likely to be produced in general. Recently, a quantum wire [11] and a Dirac billiard [12] were also used as quantum entanglers.…”
Section: Introductionmentioning
confidence: 99%
“…Because its non-classical characteristics, the control of entangled states has attracted the interest of numerous science communities 3 . The technological applications of the effect has a broad range as quantum computation, teleportation, telecommunication and cryptography [2][3][4] .A large number of mechanism to entangle electronic particles, with or without interaction, can be found in the literature 4-6 , and the quantum chaotic devices are a promising option 7,8 . In a recent work, Beenakker et al…”
mentioning
confidence: 99%
“…A large number of mechanism to entangle electronic particles, with or without interaction, can be found in the literature 4-6 , and the quantum chaotic devices are a promising option 7,8 . In a recent work, Beenakker et al…”
mentioning
confidence: 99%
See 1 more Smart Citation